O ensino da pronúncia do inglês sob um olhar cognitivo e socioculturalmente guiado: caminhos para a formação e atuação docente - Rosa, Eliane Nowinski da (Universidade do Vale do Rio dos Sinos, 2023)
This research was motivated by the desire to offer guidelines to a group of 07 Brazilian teachers who requested theoretical-methodological support to know how to treat English pronunciation in a pedagogical way in their classroom. This guidance, which has taken form of a pronunciation teaching approach, was built under the assumptions of Cognitive Phonology (LANGACKER, 1987, 2008, 2013, 2017b, 2017c) and teaching English as an International Language (JENKINS, 1998, 2000, 2001, 2002a; MCKAY, 2000, 2002, 2003, 2010, 2018; SEIDLHOFER, 2003; LLURDA, 2004; SHARIFIAN, 2009; MATSUDA, 2018; MARLINA, 2014, 2018). This study also proposed to participants an online workshop that allowed them to reflect critically on the use of the pronunciation teaching approach. In broad terms, findings presented in this study demonstrate that participants: i) did not receive instruction on pronunciation teaching in their initial teacher education; ii) wish that they had received a pedagogical training in pronunciation teaching because this knowledge would let them feel more confident and secure to teach it; iii) appreciated the principles of pronunciation teaching approach proposal; iv) enjoyed participating in a critical and reflective formation aiming to improve their teaching practice and the target approach. These results suggest that this research was able to offer the guidance requested by participants and providing space and moments for teachers to interact, reflect and dialogue in a collaborative way may be of great benefit in order to make their teaching practice better towards building a fairer, more inclusive, egalitarian, and democratic society. At the same time, it is expected that the results of this research can not only encourage further discussions on the need of empowering (future) teachers to integrate pronunciation into their daily class work, but also stimulate teachers and scholars to rethink and resignify English pronunciation teaching for a globalized world.
Keywords: Ensino de pronúncia; Língua inglesa; Ensino de inglês como língua internacional; Fonologia cognitiva; Formação docente; Pronunciation teaching; English language; Teaching english as an international language; Cognitive phonology; Teacher education; ACCNPQ::Lingüística, Letras e Artes::Lingüística